Non‐additive effect on thrombin generation when a plasma‐derived factor VIII/von Willebrand factor (FVIII/VWF) is combined with emicizumab in vitro. (25th June 2020) - Bravo, María Isabel; Raventós, Aida; Pérez, Alba; Costa, Montserrat; Willis, Todd
Abstract: Background: Emicizumab is an alternative non‐factor approach for treating patients with hemophilia A. However, there is a potential risk of thrombotic events when emicizumab is concomitantly administered with pro‐hemostatic therapies. Objectives: To assess the hemostatic effect in vitro when a plasma‐derived factor VIII concentrate containing von Willebrand factor (pdFVIII/VWF) was added to hemophilia A plasma (HAp) in combination with emicizumab. Methods: HAp and HAp with FVIII inhibitors (HAp‐i) samples with different concentrations of emicizumab (50 and 100 μg/mL) were combined with activated prothrombin complex concentrate at 0.5 to 1 U/mL, recombinant activated factor VII (rFVIIa) at 0.5 to 7 μg/mL, and pdFVIII/VWF at 0.1 to 4.5 IU/mL. Thrombin generation (TG; thrombin peak and endogenous thrombin potential) was determined using a Calibrated Automated Thrombogram assay. Results: When activated prothrombin complex concentrate was added to HAp and HAp‐i with emicizumab, TG dramatically increased (multiplier effect > 4.5×). Addition of rFVIIa to HAp or HAp‐i with emicizumab moderately increased TG in a concentration‐related manner compared with rFVIIa alone. Addition of pdFVIII/VWF to HAp or HAp‐i with emicizumab induced a TG response equivalent to those samples without emicizumab. In an in vitro model of immune tolerance induction with bleeds (HAp‐i 15 Bethesda units), combination of pdFVIII/VWF, emicizumab, and rFVIIa did not trigger a multiplying effect on TG. Conclusions: pdFVIII/VWF showed a non‐additive effect on TG when combined in vitro with emicizumab. This finding suggests that emicizumab has limited ability to promote factor X activation in the presence of pdFVIII/VWF, thus reducing the risk of thrombotic events.